PHYTOCHEMICAL SCREENING AND ANTIOXIDANT ACTIVITIES OF TANEE BANANA BLOSSOM TEA (MUSA BALBISIANA COLLA) IN CHET SAMIAN, PHOTHARAM, RATCHABURI - Chanthasri, Wipawee (Life Sciences and Environment Journal, 2025)
The aims of this study were to determine phytochemical and antioxidant activities of blossom tea (Musa balbisiana Colla) selected from Chet Samian subdistrict, Photharam district, Ratchaburi province for the development of banana blossom tea. Extracts were prepared as tea infusions brewed for 1 and 3 minutes. The results revealed the presence of phytochemicals considered such as tannin, saponin, alkaloid, terpenoid, cardiac glycoside and phlobatannin. In addition, it was found that Tanee banana blossom tea at 3 min extract exhibited the highest total phenolic content and total flavonoid content (10.84±0.20 mg GAE/g extract and 2.25±0.04 mg CE/mg extract, respectively). And also showed highest DPPH and ABTS radical scavenging capacities (IC50 values of 5.92± 0.09 mg/mL and 22.71 ± 0.47 mg/mL, respectively). There was a statistically significant difference with p ≤ 0.05. Tanee banana blossom tea at 3 min were low in Calories (1.81 Kcal/100g) and Sugar (<0.50 g/100 g). According to these results, it could be concluded that banana blossom tea at 3 min extract had great biological activities which could be applied for product development from dried banana blossom.